The role of nurses in hematopoietic stem cell transplantation (Research, Society and Development, 2021)
This study is about the role of nurses in hematopoietic stem cell transplantation. It aims to highlight the importance of nurses' work in hematopoietic stem cell transplantation. It is conceived as an integrative review developed from one guiding question: What is the nurse's role in hematopoietic stem cell transplantation when it comes to patient care? To produce the paper, an integrative literature review was carried out, with papers being selected from the Virtual Health Library, BVS Nursing Brazil, with the following descriptors on the DeCS database “Nursing Assistance”, “Nurse's Role” and “Hematopoietic Stem Cell Transplantation” in Portuguese and English between 2011 and 2020. As the exclusion criteria, articles that did not fit the proposed theme, as well as literature review articles, were discarded. As the inclusion criteria: papers published from 2011 to 2020 in Portuguese and English were used. The article was subdivided into three categories that helped to identify nurses facing hematopoietic stem cell transplantation. Such as the knowledge needed to carry out the transplant, the nurse facing palliative care, and finally, nurses' role in the psychological assessment of patients during hematopoietic stem cell transplantation. The paper found that the care provided by nurses is integral and the trained professional works at different levels, from the most basic tasks to the most complex ones, and they are protagonists in the care of patients qualified for hematopoietic stem cell transplantation.